A variable neighbourhood search algorithm for disassembly lines. Issue 2 (2nd March 2015) - Kalayci, Can B.; Polat, Olcay; Gupta, Surendra M.
Abstract : Purpose: – The purpose of this paper is to efficiently solve disassembly line balancing problem (DLBP) and the sequence-dependent disassembly line balancing problem (SDDLBP) which are both known to be NP-complete. Design/methodology/approach: – This manuscript utilizes a well-proven metaheuristics solution methodology, namely, variable neighborhood search (VNS), to address the problem. Findings: – DLBPs are analyzed using the numerical instances from the literature to show the efficiency of the proposed approach. The proposed algorithm showed superior performance compared to other techniques provided in the literature in terms of robustness to reach better solutions. Practical implications: – Since disassembly is the most critical step in end-of-life product treatment, every step toward improving disassembly line balancing brings us closer to cost savings and compelling practicality. Originality/value: – This paper is the first adaptation of VNS algorithm for solving DLBP and SDDLBP.